2012
DOI: 10.1021/pr201203m
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Proteome Changes in a DNA Repair Deficient Ercc1 Mouse Model of Accelerated Aging

Abstract: Cognitive decline is one of the earliest hallmarks of both normal and pathological brain aging. Here we used Ercc1 mutant mice, which are impaired in multiple DNA repair systems and consequently show accelerated aging and progressive memory deficits, to identify changes in the levels of hippocampal synaptic proteins that potentially underlie these age-dependent deficits. Aged Ercc1 mutant mice show normal gross hippocampal dendritic morphology and synapse numbers, and Ercc1 mutant hippocampal neurons displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 65 publications
0
24
1
1
Order By: Relevance
“…Immunoblotting was performed following a standard protocol [24]. In short, the samples were heated for 5 min at 95°C in a Laemmli sample buffer, and 7 μg of protein was loaded on a TGX stain-free gradient gel (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting was performed following a standard protocol [24]. In short, the samples were heated for 5 min at 95°C in a Laemmli sample buffer, and 7 μg of protein was loaded on a TGX stain-free gradient gel (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Whichever is the case, ROS-related changes to biomolecules are important in the pathogenesis of many serious chronic diseases including ocular disorders such as cataract, glaucoma and age-related macular degeneration (AMD) [3]. In this respect, AMD seems to be of special interest, since aging is a primary factor in its etiology, and oxidative DNA damage may be involved in premature aging [4]. Degenerative changes in retinal pigment epithelium (RPE)—a monolayer of cells between the neural retina and the retinal basement membrane (Bruch’s membrane), resulting from age-related and oxidative stress-induced damage (in RPE cells)—are an anatomical hallmark of AMD [5].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of DNA damage following Ercc1 gene inactivation results in the progeroid phenotype (2, 6). Recently, it was shown that global and neuron-specific Ercc1 mutant mice showed age-related neuronal changes in the spinal cord and the hippocampus (7,8). Here, we set out to monitor molecular changes in the cerebellum of Purkinje cell-specific Ercc1 knock-out mice by quantitative proteomics.…”
mentioning
confidence: 99%
“…Until now, most neuroproteomics studies have been directed at general protein composition of the synapse, with the emphasis on the synaptosomes (9), synaptic membranes (10,11), or post-and pre-synaptic densities (8,12) by using subcellular fractionation strategies on the whole brain or subcompartments. Here, we compared quantitatively the proteome from intact cerebella from Purkinje neuron-specific DNA-repair KO mice with cerebella from control mice at the age of 8, 16, and 26 weeks to monitor aging-related molecular changes in the cerebellum over time.…”
mentioning
confidence: 99%